Reinforcing strong coupling with hybrid microcavities for polariton chemistry application - Qureshi, Hassan Ali (2021)
The light-matter coupling is a physical phenomenon in which optical modes of light are in resonance with the energy level of matter, thus enabling exchange of energy between them. The strong light-matter coupling is achieved when energy levels of the matter are in resonance with confined light mode and they start exchanging energy in such a way that the rate of this energy exchange overcomes the energy dissipation rate of the system. This usually needs a resonance with a highly confined light mode. The strongly light-matter coupled system acquires new hybrid energy levels that are different from the matter’s energy levels. This regime offers a wide range of applications in optoelectronics and chemistry. The strong coupling has made possible the manipulation of chemical reactions without changing the chemical environment of the system, giving rise to a new branch of chemistry known as the polariton chemistry. This thesis provides comprehensive study on the enhancement of strong coupling by using hybrid cavities made up of two different materials couple to the same confined optical mode. The study includes the absorption evolution of the HBQ molecule system and a hybrid system consisting of HBQ molecule and polycrystalline ZnO. The strong coupling was achieved by depositing molecules inside the Fabry- Pérot cavity. The Rabi split energies of HBQ cavities were 205 meV, 228 meV, and 279 eV whereas, HBQ-ZnO hybrid cavities showed Rabi split energies of 300 meV and 310 meV. The study also includes the effect of strong coupling by changing the cavity geometry. The Rabi split energies in modified geometry were observed as 380 meV, 430 meV, and 490 meV.